2000
DOI: 10.1103/physrevlett.85.1839
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities in a Magneto-optical Trap: Noise-Induced Dynamics in an Atomic System

Abstract: The instabilities observed in the atomic cloud of a magneto-optical trap are experimentally studied through the dynamics of the center of mass location and the cloud population. Two dynamical components are identified: a slow, stochastic one affects both variables, and a fast, deterministic one affects only the center of mass location. A one-dimensional stochastic model taking into account the shadow effect is developed from these observations and reproduces the experimental behavior. It is shown that instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
78
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 15 publications
1
78
2
Order By: Relevance
“…However, the study of the dynamical properties of MOTs have received much attention recently, which revives the investigation of the basic properties of laser cooled gases. Examples of such a growing interest can be found in the work realized by Kim et al [5], where a parametric instability is excited by an intensity modulated laser beam, and in the works of di Steffano and co-workers [6][7][8], where the feedback of retroreflected laser beams can induce stochastic or deterministic chaos for a large optical thickness of the MOT.A route for the most intriguing complex behavior in magneto-optical traps relies exactly on the multiple scattering of light, a mechanism which have been described since the early stages of MOTs as the principal limitation for the compressibility of the cloud [9,10]. Under these circumstances, the atoms experience a mediated long-range interaction potential similar to a Coulomb potential (∼ 1/r) [11] and the system can therefore be regarded as a one-component trapped plasma.…”
mentioning
confidence: 99%
“…However, the study of the dynamical properties of MOTs have received much attention recently, which revives the investigation of the basic properties of laser cooled gases. Examples of such a growing interest can be found in the work realized by Kim et al [5], where a parametric instability is excited by an intensity modulated laser beam, and in the works of di Steffano and co-workers [6][7][8], where the feedback of retroreflected laser beams can induce stochastic or deterministic chaos for a large optical thickness of the MOT.A route for the most intriguing complex behavior in magneto-optical traps relies exactly on the multiple scattering of light, a mechanism which have been described since the early stages of MOTs as the principal limitation for the compressibility of the cloud [9,10]. Under these circumstances, the atoms experience a mediated long-range interaction potential similar to a Coulomb potential (∼ 1/r) [11] and the system can therefore be regarded as a one-component trapped plasma.…”
mentioning
confidence: 99%
“…Among these, the temporal instabilities can be both stochastic as well as deterministic. The stochastic instabilities are not really instabilities, but originate in the amplification of experimental noise through coherent resonance [6], [7]. However, the deterministic instabilities arise as a result of the beam imbalance because of the shadow effect: due to the absorption of light inside the cloud, the intensities of the backward and forward beams become locally different.…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the operating parameters, the proportion of one type of instabilities can be enhanced at the expanse of the other type [8], [9]. In addition, bistability [6][7][8][9] is the common feature of all these instabilities. Besides these temporal instabilities, the MOTs are famous for their stable spatial "modes" or distributions resulting from the lateral mismatch between the oppositely travelling beams [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies of Sesko et al, Bagnato et al have observed the limit cycles and some abrupt changes of atomic spatial distributions (Bagnato et al, 1993;Dias Nunes et al, 1996). Recently, Wilkowski et al found the instability phenomena in a MOT and explained them by means of shadow effect (Wilkowski et al, 2000;di Stefano et al, 2003). In addition, MOT exhibits very unique collective effects and critical behaviors when the number of atoms increases such as instability-induced pulsation (Labeyrie et al, 2006), and plasma oscillations of ultracold neutral plasma (Kulin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%